Molecular cytogenetic investigation of two patients with Y chromosome rearrangements and intellectual disability - Tyson, C.; Dawson, A.J.; Bal, S.; Tomiuk, M.; Anderson, T.; Tucker, D.; Riordan, D.; Chudoba, I.; Morash, B.; Mhanni, A.; Chudley, A.E.; McGillivray, B.; et al. (American journal of medical genetics. Part A, 2009)
We describe two males with intellectual disability (ID) and facial dysmorphism, both of whom have non‐mosaic Y chromosome rearrangements resulting in deletions of large portions of the Y chromosome. Patient A, with ID, mild dysmorphism, speech delay, Duane anomaly of the eye, hypermetropia and conductive hearing loss, had two structurally rearranged Y chromosomes resulting in both p and q arm deletions in addition to a Yp duplication. Patient B, also with speech and language delay, developmental delay and short stature, had an interstitial deletion of Yq11.21–11.23. Array‐CGH excluded the presence of additional submicroscopic rearrangements at the 1 Mb resolution level. A review of males with Y chromosome rearrangements and ID was performed. Our study provides a more detailed molecular cytogenetic assessment of Y rearrangements in individuals with ID than has been previously possible, and facilitates assessment and comparison of other individuals with a Y chromosome rearrangement. © 2009 Wiley‐Liss, Inc.